HOW TO ENSURE ENVIRONMENTAL AND INDUSTRIAL SAFETY IN SPACE EXPLORATION? - S. M. Sukhorukova; A. M. Pogorelyi (Российский технологический журнал)
Using the technological advances, people began space exploration with the purpose of extraction of raw materials on other planets and move there enterprises for its processing. The authors of the article express their opinion on the ineffectiveness of the "space" economy taking into account its costs and environmental impacts. Taking into account the system integrity space, it is proposed to build the economic policy of nature management on the principle of coevolutional development. You have to integrate economic theory with the science that studies the space, given the development of its components. But until that happens, the effectiveness of "space" economy proves the liberal market theory of Economics that when using the resources of the biosphere did not take into account the requirements of its system integrity as cosmoplanetary phenomenon and have caused ecological crisis on Earth.